The problems and prospects of the ukraine’s economy development in the context of european integration - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (Publishing house «BREEZE», Montreal, Canada, 2014)
The current trends, and also problems and prospects of the Ukraine's economy development in terms of European integration processes are considered in the article. Particular attention is paid to the European integration in the economic sphere. The integration of Ukraine into the EU will provide its entry to the world's most powerful regional association, which significantly affects the overall dynamics, structural changes, the level of technology and the format of the regulation of the global economy.
Keywords: national economy; European integration; competitiveness; reform; economy development; Ukraine; the European Union